Pengimplementasian Surat An-Nahl Ayat 125 Untuk Mengoptimalkan Pengetahuan Perempuan Melalui Majlis Ta’lim di Desa Bumiharja Kecamatan Tarub Kabupaten Tegal - Afikoh Maulidya; Muhamad Rifa’i Subhi (Pusat Riset dan Inovasi Nasional, 2024)
The da'wah methods that will be conveyed by the Preachers in order to achieve the da'wah objectives that have been targeted. This Majlis Ta'lim is also one of the most effective ways to invite women to join the local community so they can seek knowledge. In the Ta'lim majlis there are various activities, including reciting the reading of the iqro to the Qur'an and istighosah. This study can be said as non-formal education to increase Islamic knowledge to women. The purpose of da'wah that is adapted to the da'wah method so that these goals can run smoothly, can be adjusted to the conditions in the places that have been targeted. If it is in accordance with the desired da'wah method, it will have a positive impact and good change for the local community. The success of preaching is also encouraged by the Da'I which is related to the way in which material is delivered to the mad'u. In order to increase adaptation between Da'I and Mad'u. The da'wah method used by the local Da'I in the recitation of the Ta'lim majlis is the bil-Hikmah, bil-Mau'izah Hasanah, and bil MujJadi da'wah methods. The da'wah conveyed by the Da'I must be adjusted to the conditions of the Mad'u in Bumiharja Village. This study uses data collection techniques by interview and observation. Interviews conducted by research to Ustadz Slamet and Mad'u Majlis Ta'lim in Bumiharja Village, Tarub District. Optimizing in preaching through the interpretation of the letter An-Nahl Verse 125 (a case study of Ustadz Slamet's preaching strategy in optimizing women's knowledge in Bumharja Village, Tarub District, Tegal Regency) it can be said that Ustadz Slamet uses the da'wah method bil Hikmah, bil Mau'izah Hasanah and bil Muj is where Ustadz Slamet was staying, he always looked at the condition of the local Mad'u so that he could find supporting factors for his missionary goals. One of them is Ustadz Slamet's way of presenting the material by using words that are easy to understand and polite and smooth so that the Mad'u can quickly accept it.